If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + -2)(2x + 5) = 36 Reorder the terms: (-2 + 3x)(2x + 5) = 36 Reorder the terms: (-2 + 3x)(5 + 2x) = 36 Multiply (-2 + 3x) * (5 + 2x) (-2(5 + 2x) + 3x * (5 + 2x)) = 36 ((5 * -2 + 2x * -2) + 3x * (5 + 2x)) = 36 ((-10 + -4x) + 3x * (5 + 2x)) = 36 (-10 + -4x + (5 * 3x + 2x * 3x)) = 36 (-10 + -4x + (15x + 6x2)) = 36 Combine like terms: -4x + 15x = 11x (-10 + 11x + 6x2) = 36 Solving -10 + 11x + 6x2 = 36 Solving for variable 'x'. Reorder the terms: -10 + -36 + 11x + 6x2 = 36 + -36 Combine like terms: -10 + -36 = -46 -46 + 11x + 6x2 = 36 + -36 Combine like terms: 36 + -36 = 0 -46 + 11x + 6x2 = 0 Factor a trinomial. (-23 + -6x)(2 + -1x) = 0Subproblem 1
Set the factor '(-23 + -6x)' equal to zero and attempt to solve: Simplifying -23 + -6x = 0 Solving -23 + -6x = 0 Move all terms containing x to the left, all other terms to the right. Add '23' to each side of the equation. -23 + 23 + -6x = 0 + 23 Combine like terms: -23 + 23 = 0 0 + -6x = 0 + 23 -6x = 0 + 23 Combine like terms: 0 + 23 = 23 -6x = 23 Divide each side by '-6'. x = -3.833333333 Simplifying x = -3.833333333Subproblem 2
Set the factor '(2 + -1x)' equal to zero and attempt to solve: Simplifying 2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2Solution
x = {-3.833333333, 2}
| 3y-6+90=180 | | 13=4x-14 | | -10=-8h-2 | | 6(5x+9)=144 | | 3/4g | | 2(x-3)=3x+5 | | 2p^2-43+225=0 | | 2x+2=6+x | | R^2+10t=-22 | | 8+7x=4x+32 | | -3(3x+w)+3(6w+2x)= | | 1600=5100-700x | | x/3+9=16 | | 1600=700x-5100 | | 7y+2=.333333333(9y+282) | | 10+7x=4x+16 | | 4/9-4/3v=-1/2 | | 4x+7=7x-29 | | 2*5a+1=2*a+1 | | y=1/2*1/2 | | 6n+68=7n-2(n-2) | | 3(-1+2)=6x+9 | | -1/5u-5/2=-4/3 | | 5+5x+2x=5 | | 80y^2-120y= | | -4y-4=4(y+9) | | 2*x-3=x+5 | | (2x+1)*(2x+3)+7+3= | | 5x+3+3x=91 | | 5(u+2)=9u+18 | | (2y+x)^3/5 | | 5+7x+2x=86 |